Optimizing Mixed Farming Systems for Enhanced Productivity, Nutrition, Income, Environmental Sustainability, and Social Inclusion: A Field Day Report - Tessema, Fikadu; Gebreyes, Million; Mekonnen, Kindu (International Livestock Research Institute, 2024)
In Ethiopia, mixed farming systems involve both crop cultivation and livestock raising. This approach is critical for many Ethiopian farmers' livelihoods, especially in the highlands, where agricultural practices are significantly influenced by environmental factors like climatic, edaphic, anthropogenic, socio-economic, institutional, and environmental conditions. As a result of these challenges, it is apparent to see huge food-feed gaps in these mixed farming systems. Land degradation, population pressure, land size, poor infrastructure, shortages of demand and niche compatible technologies, inadequate job opportunities for youth and weak input-output market are also some of the challenges that affect the productivity of the mixed farming systems. Mixed Farming Systems (MFS) initiative, and AICCRA and TAAT projects have been jointly working with Regional (Central Ethiopia Agricultural Research Institute (CEARI), Workable Agricultural Research Center, Hadiya Zone Department of Agriculture, Lemo Woreda Office of Agriculture) and international organizations (ILRI, CIAT, Alliance Bioversity and ICARDA) and providing practical solution on climate smart feed-food innovations approach in Lemo and Misha Woredas of Hadiya Zone, Central Regional State Ethiopia. To disseminate research interventions and findings; field day is an instrument in sharing food and forage technologies in Lemo woreda and the surrounding areas. It provides a platform for knowledge exchange, practical demonstrations, and peer learning, empower farmers to embrace model agricultural practices, ultimately leading to improved productivity, nutrition, and income.